Novel Risk Score for Fetuses with Congenital Diaphragmatic Hernia Based on Ultrasound Findings - Terui, Keita; Nagata, Kouji; Hayakawa, Masahiro; Okuyama, Hiroomi; Amari, Shoichirou; Yokoi, Akiko; Masumoto, Kouji; Urushihara, Naoto; Okazaki, Tadaharu; Inamura, Noboru; Toyoshima, Katsuaki; Uchida, Keiichi; Furukawa, Taizo; Okawada, Manabu; Sato, Yasunori; Usui, Noriaki (European Journal of Pediatric Surgery, 2020)
Introduction We aimed to establish and validate a risk score for fetuses with congenital diaphragmatic hernia (CDH) using only prenatal ultrasound findings.Material and Methods Derivation (2011–2016, n = 350) and validation (2006–2010, n = 270) cohorts were obtained from a Japanese CDH study group database. Using a logistic regression analysis, we created a prediction model and weighted scoring system from the derivation dataset and calculated the odds ratio of an unsatisfactory prognosis (death within 90 days of life or hospitalization duration exceeding 180 days). Five adverse prognostic factors obtained using prenatal ultrasound, including an observed/expected lung area-to-head circumference ratio (o/eLHR) <25%, liver herniation occupying more than one-third of the thoracic space, thoracic stomach, right-side CDH, and severe malformations, were used as predictors. The obtained model was validated using the validation cohort.Results The unsatisfactory prognosis prediction model was obtained based on the adjusted odds ratios. The C statistics of the model were 0.83 and 0.80 in the derivation and validation datasets, respectively. The five variables were weighted proportionally to their adjusted odds ratios for an unsatisfactory prognosis (o/eLHR <25%, 1 point; liver herniation occupying more than one-third of the thoracic space, 1 point; thoracic stomach, 1 point; right-side CDH, 2 points; and severe malformations, 3 points). Unsatisfactory prognosis rates for the low- (0–2 points), intermediate- (3–5 points), and high-risk (6–8 points) groups were 17, 46, and 100%, respectively (p < 0.001), in the validation cohort.Conclusion Our simple risk score effectively predicted the prognosis of fetuses with CDH.
Keywords: congenital diaphragmatic hernia; fetus; prognosis; morbidity